The Exclusionary Rule in Germany - Bradley, Craig M. (1983)
The exclusionary rule that the Supreme Court has fashioned to suppress evidence obtained unconstitutionally is directed at least in part toward deterring police conduct that violates constitutional norms. Since the inception of the rule, the value and efficacy of a prescript that excludes otherwise relevant and probative evidence in a factfinding proceeding has been a subject of heated debate. In this Article, Professor Bradley examines the rather different exclusionary rules used in Germany. He argues that a comparison of exclusionary rules in Germany and the United States suggests that a number of different policies of a criminal justice system could inspire such rules but that the two countries share the ultimate goal of protecting the constitutional rights of the accused